2017
DOI: 10.23937/2572-4053.1510017
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Nightmares and Schizophrenia

Abstract: Sleep problems are recognized as widespread in patients with psychosis. Other facts are known as well -that not only can psychiatric illness result in sleep problems, but that these same problems can exacerbate psychopathology and that they constitute risk factors for suicide. Sleep difficulties are known to respond well to appropriate treatment and yet, with the exception of insomnia, sleep quality is not routinely inquired about during psychiatric assessments. This narrative review focuses on nightmares in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
(77 reference statements)
0
1
0
1
Order By: Relevance
“…Reeve et al [ 44 ] found the prevalence in early schizophrenia to be very high (48.3%), with no association to antipsychotic medication. It has been suggested that nightmares in schizophrenia are a continuation into sleep of frightening daytime delusions [ 58 ]. This raises the hope that, if nightmares were cured, daytime delusions would also abate [ 59 ].…”
Section: Sleep and Psychosismentioning
confidence: 99%
“…Reeve et al [ 44 ] found the prevalence in early schizophrenia to be very high (48.3%), with no association to antipsychotic medication. It has been suggested that nightmares in schizophrenia are a continuation into sleep of frightening daytime delusions [ 58 ]. This raises the hope that, if nightmares were cured, daytime delusions would also abate [ 59 ].…”
Section: Sleep and Psychosismentioning
confidence: 99%
“…L'American Academy of Sleep Medicine recommande comme traitement le prazosin (un antagoniste des récepteurs adrénergiques alpha 1), mais également la TCC-i. Les traitements psychologiques des cauchemars semblent agir par l'augmentation du sentiment de contrôle, une diminution de la peur, la restauration du sommeil et la restructuration de croyances inappropriées (Seeman, 2017). La thérapie cognitivo-comportementale des cauchemars pour la population schizophrène est une avenue prometteuse de traitement (Sheaves et coll., 2019).…”
Section: Syndrome D'apnées/hypopnées Du Sommeilunclassified